ATN profiles among cognitively normal individuals and longitudinal cognitive outcomes. (2nd April 2019) - Soldan, Anja; Pettigrew, Corinne; Fagan, Anne M.; Schindler, Suzanne E.; Moghekar, Abhay; Fowler, Christopher; Li, Qiao-Xin; Collins, Steven J.; Carlsson, Cynthia; Asthana, Sanjay; Masters, Colin L.; Johnson, Sterling; et al.
Abstract : Objective: To examine the long-term cognitive trajectories of individuals with normal cognition at baseline and distinct amyloid/tau/neurodegeneration (ATN) profiles. Methods: Pooling data across 4 cohort studies, 814 cognitively normal participants (mean baseline age = 59.6 years) were classified into 8 ATN groups using baseline CSF levels of β-amyloid 1–42 as a measure of amyloid (A), phosphorylated tau 181 as a measure of tau (T), and total tau as a measure of neurodegeneration (N). Cognitive performance was measured using a previously validated global factor score and with the Mini-Mental State Examination. We compared the cognitive trajectories across groups using growth curve models (mean follow-up time = 7 years). Results: Using different model formulations and cut points for determining biomarker abnormality, only the group with abnormal levels of amyloid, tau, and neurodegeneration (A+T+N+) showed consistently greater cognitive decline than the group with normal levels of all biomarkers (A−T−N−). Replicating prior findings using the 2011 National Institute on Aging–Alzheimer's Association/suspected non–Alzheimer disease pathophysiology schema, only individuals with abnormal levels of both amyloid and phosphorylated tau 181 or total tau (stage 2) showed greater cognitive decline than those with normal biomarker levels (stage 0). Conclusion: The results are consistent with the hypothesis that both elevated brain amyloid and neurofibrillary tangles are necessary to observe accelerated neurodegeneration, which in turn leads to cognitive decline.